Incidental Papillary Bladder Carcinoma on 18F-Fluoromethylcholine PET/CT Undertaken to Evaluate Prostate Malignancy. (September 2017) - Parekh, Amit; Hagan, Ian; Capaldi, Lisa; Lyburn, Iain
Abstract : Abstract: FDG PET is known to have a low sensitivity for the detection of prostate and bladder tumors because of high levels of urinary excretion, which potentially obscures sites of disease. Fluoromethylcholine PET has a higher sensitivity for the detection of metastatic prostate cancer compared with 18 F-FDG PET, partly because of lower levels of urinary excretion. We present a case of a patient who underwent 18 F-fluoromethylcholine PET for possible recurrent prostate cancer. The study identified an incidental, avid metachronous bladder tumor. We discuss the potential use of fluoromethylcholine PET in the detection of bladder tumors.